Coaxial transmission lines: development test of procedures for concrete - Millard, S. G.; Al-Qadi, I. L.; Shaw, M. R.; Riad, S. M.; Shaari, A.; Bungey, J. H. (ASCE Publications, 2001)
The use of ground-penetrating radar as a nondestructive investigative technique has gained increasing acceptance both in the United States and in Europe for assessing the structural integrity of concrete structures. However, without an accurate knowledge of the electrical properties of concrete at radar frequencies, it is difficult to quantitatively assess the results of a ground-penetrating radar survey. This paper reports the simultaneous, but independent, developments of two coaxial transmission line systems at Virginia Tech and The University of Liverpool. Both are designed to measure the relative permittivity and conductivity of concrete over a range of frequencies from 100 MHz to 1 GHz. This paper discusses the development of the two transmission lines, and a comparison of the two methods of measurement and interpretation of results.